Human papillomavirus and p16 immunostaining, prevalence and prognosis of squamous carcinoma of unknown primary in the head and neck region. Issue 6 (19th February 2019) - Ren, Jianjun; Yang, Wen; Su, Jie; Ren, Xue; Fazelzad, Rouhi; Albert, Tiong; Habbous, Steven; Goldstein, David P; de Almeida, John R.; Hansen, Aaron; Jang, Raymond; Bratman, Scott V.; et al.
Abstract : The prevalence of human papillomavirus (HPV) in squamous cell carcinoma of unknown primary in the head and neck (SCCUPHN), and prognosis by HPV status of SCCUPHN patients has been difficult to estimate because of the rarity of this subtype. In MEDLINE, Epub Ahead of Print, In‐Process & Other Non‐Indexed Citations, EMBASE, Cochrane library and Web of Science searches, observational studies and clinical trials that reported survival rates of patients with SCCUPHN by HPV status were identified. Meta‐analysis estimated the prevalence and prognosis (overall survival, OS; progression‐free survival, PFS) of SCCUPHN by HPV status, and compared them to studies of oropharyngeal squamous cell carcinoma (OPSCC) from the same institutions and across continents. In 17 SCCUPHN studies (n = 1, 149) and 17 institution‐matched OPSCC studies (n = 6, 522), the pooled HPV prevalence of SCCUPHN was 49%, which was only 10% (95%CI: 1–19%) lower than OPSCC prevalence in the underlying population. Estimated 5‐year OS for HPV‐negative SCCUPHN was 44% (95%CI: 36–51%) vs . HPV‐positive SCCUPHN of 91% (95%CI: 86–96%); hazard ratio (HR) for OS was 3.25 (95%CI: 2.45–4.31) and PFS was 4.49 (95%CI: 2.88–7.02). HRs by HPV status for OPSCC were similar to that in SCCUPHN. While North American SCCUPHNs had higher HPV prevalence than European SCCUPHNs (OR = 2.68 (95%CI: 1.3–5.6)), HR of OS for HPV‐negative vs . HPV‐positive patients were similar in both continents (HRs of 3.78–4.09). Prevalence of HPV among SCCUPHN patients were lower than in OPSCC. The survival benefit conferred by being HPV‐positive was similar in SCCUPHN as in OPSCCs, independent of continent.